Strengthening clinical bacteriology laboratory diagnostics to combat sepsis and antimicrobial resistance in Benin: a train-the-trainer approach - Koudokpon, Hornel; Legba, Brice Boris; Dougnon, Victorien; Mero, Sointu; Bankole, Honoré; Haukka, Kaisa (Frontiers in Medicine, 2024)
Improved laboratory diagnostics is needed to support sepsis diagnosis and combat increasing antibiotic resistance in Benin. We trained clinical laboratory experts and technicians to improve their skills in accurate and up-to-date diagnostics. A Train-the-Trainer (TtT) approach was used to design the course that combines theoretical and practical laboratory skills, specifically addressing the knowledge gaps we had previously identified in our national survey. Pedagogical methods were student-centered, including peer learning, use of online materials, practical laboratory work and pre- and post-course tests. We first trained 10 trainers who in turn trained 40 laboratory technicians from across the country, from both public and private clinical and veterinary laboratories. The trainers also prepared standard operation procedures for blood culture and antibiotic susceptibility testing based on international standards. Three months after the training, follow-up visits were made to the laboratories where the implementation of the new skills was evaluated. The progress of the participants observed during the course and the implementation of the new skills afterwards proved the training to be effective. The professional network s created during the training, the empowerment that utilizes local knowledge resources, and the government support for our initiative can be expected to bring sustainability to the initiative and support the participation of Beninese laboratories in international surveillance programs in the future.